2015
DOI: 10.1063/1.4928658
|View full text |Cite
|
Sign up to set email alerts
|

Spin- and valley-coupled electronic states in monolayer WSe2 on bilayer graphene

Abstract: We have fabricated a high-quality monolayer WSe2 film on bilayer graphene by epitaxial growth, and revealed the electronic states by spin-and angle-resolved photoemission spectroscopy. We observed a direct energy gap at the Brillounin-zone corner in contrast to the indirect nature of gap in bulk WSe2, which is attributed to the lack of interlayer interaction and the breaking of spaceinversion symmetry in monolayer film. A giant spin splitting of ∼0.5 eV, which is the largest among known monolayer transition-me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…The pure 1 H phase shows a sizable gap below the Fermi level; it is therefore a semiconductor similar to the bulk case 21 . The top valence band at splits into two branches toward because of the strong spin–orbit coupling of W. The valence band maximum is at , consistent with prior studies of this phase 24,26 . For the mixed sample, the 1 T ′ phase gives rise to additional valence bands of very different dispersion relations, and the topmost valence band reaches near the Fermi level to form a fairly flat portion around the zone center.…”
Section: Resultssupporting
confidence: 86%
“…The pure 1 H phase shows a sizable gap below the Fermi level; it is therefore a semiconductor similar to the bulk case 21 . The top valence band at splits into two branches toward because of the strong spin–orbit coupling of W. The valence band maximum is at , consistent with prior studies of this phase 24,26 . For the mixed sample, the 1 T ′ phase gives rise to additional valence bands of very different dispersion relations, and the topmost valence band reaches near the Fermi level to form a fairly flat portion around the zone center.…”
Section: Resultssupporting
confidence: 86%
“…This behavior is characteristic of a TMD ultrathin film, as has been observed in monolayer WSe 2 and TiSe 2 on bilayer graphene. 23,24 STM revealed the formation of monolayer NbSe 2 islands (Figure 1d), whose height (~0.7 nm; see line profile in Figure 1e) was nearly equal to the distance between adjacent NbSe 2 layers in bulk 2H-NbSe 2 , 0.63 Å. 10 We found that this film was composed of two different types of islands.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1b shows the reflection high-energy electron diffraction pattern of bilayer graphene on 6H-SiC(0001), which signified a 1 × 1 streak pattern and 6 ffiffi ffi 3 p 6 ffiffi ffi 3 p R30 3 spots originating from the bilayer graphene and the buffer layer beneath it, respectively. 23,24 After co-evaporation of Nb and Se atoms onto a substrate kept at 530°C in ultrahigh vacuum, the reflection highenergy electron diffraction intensity of 6 ffiffi ffi 3 p 6 ffiffi ffi 3 p R30 3 spots was reduced and a new 1 × 1 pattern appeared (Figure 1c). This behavior is characteristic of a TMD ultrathin film, as has been observed in monolayer WSe 2 and TiSe 2 on bilayer graphene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…94.201121 Understanding and controlling electrons in reduced dimensions, for example, at the interfaces between disparate semiconductors, underpins modern electronic devices [1][2][3][4]. In recent years, this has found renewed prominence through the study of electrons naturally confined in atomically thin layers, such as in graphene or monolayer transition-metal dichalcogenides, opening prospects to achieve novel functionality such as ultrafast electronic [5], spintronic, or valleytronic devices [6][7][8][9][10][11]. To progress towards these goals, it is critical to understand the behavior of electrons in two-dimensional (2D) solids, and the influence of many-body interactions between them.…”
mentioning
confidence: 99%